Do Supra-National Competition Authorities Resolve the Challenges of Cross Border Merger Regulation in Developing and Emerging Economies? The Case of the Common Market for Eastern and Southern Africa. - Mwemba, Willard (Department of Commercial Law, 2021)
The case for cross-border merger control and the need for a supranational merger control system has been debated upon and several scholars have written extensively on the subject. What is immediately evident from literature is that it is not easy to regulate such mergers because of the challenges encountered. The challenges are pronounced in developing and emerging economies (DEEs) as arguably they have less experience in the enforcement of merger laws and lack adequate resources for such an exercise. Other challenges identified from publicly available information are the lack of extra territorial application of national competition laws to conduct taking place outside their borders, limited skills and expertise and poor cooperation and coordination arrangements among the jurisdictions involved. Further cross-border merger regulation presents challenges to merging parties too due to their exposure to different national competition laws. The dissertation focuses on whether supra-national competition authorities address the challenges of cross-border merger regulation in DEEs. However, there are a number of supranational competition authorities established by DEEs that generalising the study would be an unrealistic and impractical task to undertake. In view of this, the Common Market for Eastern and Southern Africa (COMESA) was selected as a sample because it is the regional economic community that has recently established a fully operational supra-national competition authority to regulate inter alia, cross border mergers. Further, all COMESA Member States are DEEs which provides to a greater degree a relatively uniform sample.